Kant on representation and objectivity - Dickerson, A. B. (Cambridge University Press, 2004)
"This book is a study of the second-edition version of the 'Transcendental Deduction' (the so-called 'B-Deduction'), which is one of the most important and obscure sections of Kant's Critique of Pure Reason. By way of a close analysis of the B-Deduction, A.B. Dickerson makes the distinctive claim that the Deduction is crucially concerned with the problem of making intelligible the unity possessed by complex representations - a problem that is the representationalist parallel of the semantic problem of the unity of the proposition